High-nickel oxide positive electrode material with two-phase symbiotic structure and preparation method of high-nickel oxide positive electrode material

By using two-phase symbiotic structure and one-step spray pyrolysis method in high-nickel oxide positive electrode materials, the problems of material structural stability and preparation process complexity are solved, and higher mechanical stability, rate performance and cycle life are achieved, while reducing production costs.

CN119551738APending Publication Date: 2025-03-04YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411672946.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing high-nickel oxide positive electrode materials have poor structural stability, and the preparation process is complex and time-consuming, high cost and poor consistency.

Method used

Using the preparation method of high nickel oxide positive electrode material with a two-phase symbiotic structure, atomizing the reaction solution into nano droplets and performing a one-step reaction in a dual-temperature pyrolysis reactor, a two-phase symbiotic structure with a layered structure and a spinel structure is formed.

Benefits of technology

It significantly improves the mechanical stability and thermodynamic stability of the material, inhibits uncontrollable interface side reactions and oxygen release, improves rate performance and cycle life, and simplifies the process flow and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551738A_ABST
    Figure CN119551738A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and discloses a high-nickel oxide positive electrode material with a two-phase symbiotic structure and a preparation method, the unique two-phase symbiotic structure can effectively inhibit the violent change of the unit cell volume in the charging and discharging process, and the mechanical stability of the material is improved; a spinel structure is controllably constructed in advance, so that the reaction activity of the material can be effectively reduced, and the thermodynamic stability is improved, thereby inhibiting uncontrollable interface side reaction, oxygen release and irreversible phase change; due to the nanocrystallized particle morphology, faster lithium ion transmission can be realized, and the rate capability of the material is improved; the one-step spray pyrolysis method has the advantages of simple process, rapid reaction, no need of complex steps of coprecipitation, filtration, washing, crushing, calcination and the like, no generation of wastewater, great improvement of the production efficiency and reduction of the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a high-nickel oxide positive electrode material with a two-phase symbiotic structure and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high operating voltage, high energy / volume density, no memory effect, and low self-discharge, and have been widely used in consumer electronics, electric vehicles, and energy storage. The positive electrode material is one of the key materials that determine the performance of lithium-ion batteries. With the advantage of high specific energy, high nickel oxide positive electrode materials (LiNi x M y O2, where x+y=1, 0.8≤x<1, and M is one or more of Co, Mn, Al, Zr, W, Sb, Ta, and Ti), has been widely used in power lithium-ion batteries pursuing high energy density.

[0003] At present, most high-nickel oxide cathode materials are layered structures belonging to the R-3m space group. Among them, oxygen atoms are cubically densely packed, occupying the 6c position; lithium ions and transition metal ions alternately occupy the oxygen octahedral voids at the 3a and 3b positions, presenting a layered structure of alternating lithium layers and transition metal layers.

[0004] At present, high nickel oxide cathode materials are mainly prepared by co-precipitation-high temperature solid phase method. First, the transition metal salt solution is co-precipitated with alkali solution and complexing agent to prepare hydroxide precursor; then, the hydroxide precursor is solid-phase calcined with lithium salt at high temperature to obtain the final high nickel oxide cathode material.

[0005] Through the above analysis, the problems and defects of the prior art are as follows:

[0006] (1) The structural stability of layered high nickel oxide cathode materials is poor

[0007] On the one hand, the layered structure material will undergo H2-H3 phase transition during high potential charging, and the sharp contraction of the c-axis will cause a drastic change in the unit cell volume, affecting the mechanical stability of the material; on the other hand, due to the Ni 4+ -O bonds are highly reactive and thermodynamically unstable, and layered materials are prone to spontaneous reduction at high potentials (Ni 4+ / Ni 2+ ) or undergo interfacial side reactions with the electrolyte, accompanied by oxygen release and irreversible phase transition (layered-spinel phase transition), which affects the structural stability and performance of the material.

[0008] (2) The existing co-precipitation-high temperature solid phase method has problems such as long time consumption, high cost and poor consistency.

[0009] On the one hand, the preparation process of the co-precipitation-high temperature solid phase method is complicated, time-consuming and costly; on the other hand, there are many parameters that affect the reaction process (such as solution concentration, feed rate, co-precipitation temperature, co-precipitation pH value, co-precipitation atmosphere, co-precipitation speed, calcination temperature, heating rate, calcination atmosphere, etc.), and the control requirements are strict, resulting in poor consistency in component distribution and morphology and particle size. Summary of the invention

[0010] In view of the problems existing in the prior art, the present invention provides a high-nickel oxide positive electrode material with a two-phase symbiotic structure and a preparation method.

[0011] The present invention is achieved by: a method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure comprising:

[0012] Step 1, preparing a reaction solution: dissolving a Li source, a Ni source, a M source, an organic complexing agent, and a reaction regulating agent in deionized water to prepare a reaction solution;

[0013] Step 2, atomizing the above reaction solution into nano droplets, entering the pyrolysis reactor with the carrier gas, and a series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally a high nickel oxide positive electrode material with a two-phase symbiotic structure is collected at the tail end.

[0014] Furthermore, the high nickel oxide positive electrode material:

[0015] (1) The general chemical formula of the material is LiNi x M y O2, wherein x+y=1, 0.8≤x<1, and M is one or more of Co, Mn, Al, Zr, W, Sb, Ta, and Ti;

[0016] (2) The material is nanoparticles with an average particle size range of 50 <D 50 <150nm;

[0017] (3) The material is a two-phase intergrowth structure of layered structure and spinel structure, in which the layered structures are wedged into each other with the jagged ends of the spinel structure region as the connection point;

[0018] (4) The spinel structure belongs to the Fd-3m space group, the oxygen atoms are face-centered cubic close-packed, the transition metal ions occupy 1 / 2 of the oxygen octahedral voids, and the lithium ions occupy 1 / 8 of the oxygen tetrahedral voids.

[0019] Furthermore, the Li source is one or more of Li carboxylates, nitrates, and chlorides, and the molar ratio of Li to the total amount of Ni and M elements is 1.0-1.1:1.

[0020] The Ni source and the M source are one or more of carboxylates, nitrates and chlorides of Ni and M, respectively, and the total concentration of Ni and M ions in the reaction solution is 1-15 mol / L.

[0021] The organic complexing aid is one or more of citric acid and urea, and the molar ratio of the organic complexing aid to the total amount of Ni and M elements is 0.3-0.7:1.

[0022] The reaction regulating aid is one or more of ammonia water and lithium sulfate, and the molar ratio of the reaction regulating aid to the total amount of Ni and M elements is 0.01-0.10:1.

[0023] Furthermore, the average particle size of the nano droplets is controlled at 70 <D 50 <200nm.

[0024] Furthermore, the pyrolysis reactor is controlled by dual temperature zones, the temperature of the front temperature zone is controlled at 150-250°C, and the temperature of the rear temperature zone is controlled at 600-1000°C;

[0025] The residence time of the nano droplets in the pyrolysis reactor is 30-120s;

[0026] The carrier gas is an oxygen-containing atmosphere, and the oxygen content is 20-100%.

[0027] Another object of the present invention is to provide a lithium-ion battery containing a high-nickel oxide positive electrode material of the two-phase symbiotic structure.

[0028] Another object of the present invention is to provide a system for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure, comprising:

[0029] The preparation module is used to prepare the reaction solution: dissolve the Li source, Ni source, M source, organic complexing agent, and reaction regulating agent in deionized water to prepare the reaction solution;

[0030] The pyrolysis module is used to atomize the above reaction solution into nano droplets, which enter the pyrolysis reactor with the carrier gas. A series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally a high-nickel oxide positive electrode material with a two-phase symbiotic structure is collected at the tail end.

[0031] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0032] First, in view of the technical problems existing in the above-mentioned prior art, some creative technical effects are brought about after solving the problems. The specific description is as follows:

[0033] 1. The unique two-phase symbiotic structure can effectively suppress the drastic change of the unit cell volume during charging and discharging, and improve the mechanical stability of the material;

[0034] 2. By constructing the spinel structure in advance and in a controllable manner, the reactivity of the material can be effectively reduced and the thermodynamic stability can be improved, thereby inhibiting uncontrollable interfacial side reactions, oxygen release, and irreversible phase changes;

[0035] 3. Nano-sized particle morphology can achieve faster lithium ion transmission and improve the rate performance of the material;

[0036] 4. The one-step spray pyrolysis process is simple and has a rapid reaction. It does not require complicated steps such as co-precipitation, filtration, washing, crushing, calcination, etc. It does not produce wastewater and can greatly improve production efficiency and reduce costs.

[0037] 5. Since the droplets do not have time to segregate components during the rapid reaction process, the spray pyrolysis method can ensure the consistency of component distribution and morphology and particle size;

[0038] 6. The introduction of organic complexing additives can not only regulate the viscosity and surface tension of the droplets by complexing with metal ions, but also provide calorific value to promote uniform heating of the droplets, thereby further improving the component distribution of the material and the consistency of the morphology and particle size;

[0039] 7. The introduction of reaction regulating additives can regulate the priority of surface precipitation reaction and bulk precipitation reaction of droplets, promote ion migration and the formation of spinel-like structure.

[0040] Second, the expected benefits and commercial value of the technical solution of the present invention after transformation are:

[0041] The technical solution of the present invention can achieve a breakthrough in the application technology research field of domestic and foreign low-cost manufacturing technology of high-nickel oxide positive electrode materials with high structural stability, and can lay a solid technical foundation for future industrialization work. After the transformation of the relevant technical solution, it can form the ability to provide medium-scale samples to well-known companies in the field of energy storage at home and abroad, and promote the development and progress of domestic high-energy density and high-power density lithium-ion batteries. With the advantages of high structural stability, good rate performance, high specific capacity, high safety performance, and low manufacturing cost, the relevant products are expected to be promoted in the fields of high-energy density electric vehicle power batteries, 5G base station backup power supplies, smart grid peak-valley load regulation, energy storage power stations, etc., and have broad application prospects and commercial value.

[0042] Thirdly, the present invention provides a method for preparing a high-nickel oxide cathode material with a two-phase symbiotic structure. Through precise design and process optimization, it solves the technical problems of high-nickel cathode materials in terms of stability, preparation complexity, particle uniformity, etc. The material adopts a design in which a layered structure and a spinel structure are interwedged, with the serrated ends of the spinel region as connection points. This structure significantly improves the structural stability of the material while retaining the high-capacity characteristics of the layered structure, meeting the requirements of lithium-ion batteries for high-performance cathode materials.

[0043] The preparation method uses the aerosol pyrolysis method. By atomizing the reaction solution into nano-droplets and performing a one-step reaction in a two-temperature zone pyrolysis reactor, the preparation of the material is completed. In the front temperature zone (150 - 250 °C) of the reactor, the evaporation of the droplets and the preliminary reaction are completed, and in the rear temperature zone (600 - 1000 °C), high-temperature pyrolysis and crystallization are completed, ensuring the two-phase symbiotic structure of the material. This method simplifies the traditional multi-step process, reduces energy consumption and equipment investment costs, and improves production efficiency at the same time.

[0044] The present invention realizes precise control of the nano-particle particle size and regulation of the spinel phase ratio by using specific organic complexing aids (such as citric acid, urea) and reaction regulation aids (such as ammonia water, lithium sulfate). The average particle size range of the material is 50 < D50 < 150 nm, and the nano-droplet particle size is 70 < D50 < 200 nm, ensuring the uniformity of particle distribution and the optimization of electrochemical performance.

[0045] Compared with traditional high-nickel cathode materials, the two-phase symbiotic structure of the present invention significantly improves the cycle life and rate performance of the material. The spinel phase provides excellent mechanical stability and charge transfer ability, suppressing volume changes and phase transitions during charge and discharge, enabling the performance of the material to be improved by more than 30% under high-rate conditions, and at the same time, the cycle life is extended by more than 20%. These improvements make it more suitable for applications in fields such as consumer electronic devices, energy storage systems, and electric vehicles.

[0046] In addition, the preparation process conforms to the concept of green manufacturing. An oxygen-containing atmosphere with an oxygen content of 20 - 100% is used as the carrier gas, ensuring the oxidation uniformity and environmental friendliness of the material. High-pollution reagents are not used in the pyrolysis process, and the emissions of waste gas and waste liquid are significantly reduced, meeting environmental protection requirements. The production cost is reduced by 25% compared with the traditional method, providing an economic guarantee for the large-scale industrialization of high-nickel cathode materials.

[0047] In summary, the present invention fills the technical gaps in the stability, economy, and application scope of high-nickel oxide cathode materials. Through innovative structural design and simplified process flow, it solves the limitations of traditional high-nickel cathode materials in terms of performance and cost, and significantly promotes the progress and application expansion of lithium-ion battery technology. Brief Description of the Drawings

[0048] Figure 1 It is a flow chart of a method for preparing a high-nickel oxide positive electrode material with a two-phase symbiotic structure provided in an embodiment of the present invention.

[0049] Figure 2 It is a schematic diagram of a layered structure provided by an embodiment of the present invention.

[0050] Figure 3 It is a schematic diagram of the spinel structure provided by an embodiment of the present invention.

[0051] Figure 4 It is a schematic structural diagram of a high nickel oxide positive electrode material with a two-phase symbiotic structure provided by an embodiment of the present invention.

[0052] Figure 5 It is a structural block diagram of a system for preparing a high-nickel oxide positive electrode material with a two-phase symbiotic structure provided in an embodiment of the present invention.

[0053] Figure 6 It is a comparison chart of the cycle performance of the traditional layered structure NCM811 material and the two-phase symbiotic structure NCM811 material provided by the embodiment of the present invention. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0055] like Figure 1 As shown, a method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure provided in an embodiment of the present invention comprises the following steps:

[0056] S101, preparing a reaction solution: dissolving a Li source, a Ni source, a M source, an organic complexing agent, and a reaction regulating agent in deionized water to prepare a reaction solution;

[0057] S102, atomizing the reaction solution into nano droplets, and entering the pyrolysis reactor with the carrier gas, where a series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally a high nickel oxide positive electrode material with a two-phase symbiotic structure is collected at the tail end.

[0058] like Figure 2 , Figure 3 , Figure 4 The high nickel oxide positive electrode material provided by the embodiment of the present invention is shown as follows:

[0059] (1) The general chemical formula of the material is LiNi x M yO2, wherein x+y=1, 0.8≤x<1, and M is one or more of Co, Mn, Al, Zr, W, Sb, Ta, and Ti;

[0060] (2) The material is nanoparticles with an average particle size range of 50 <D 50 <150nm;

[0061] (3) The material is a two-phase intergrowth structure of layered structure and spinel structure, in which the layered structures are wedged into each other with the jagged ends of the spinel structure region as the connection point;

[0062] (4) The spinel structure belongs to the Fd-3m space group, the oxygen atoms are face-centered cubic close-packed, the transition metal ions occupy 1 / 2 of the oxygen octahedral voids, and the lithium ions occupy 1 / 8 of the oxygen tetrahedral voids.

[0063] The Li source provided in the embodiment of the present invention is one or more of Li carboxylates, nitrates, and chlorides, and the molar ratio of Li to the total amount of Ni and M elements is 1.0-1.1:1

[0064] Wherein, the Ni source and the M source are one or more of Ni and M carboxylates, nitrates, and chlorides, respectively, and the total concentration of Ni and M ions in the reaction solution is 1-15 mol / L;

[0065] The organic complexing aid is one or more of citric acid and urea, and the molar ratio of the organic complexing aid to the total amount of Ni and M elements is 0.3-0.7:1.

[0066] The reaction regulating aid is one or more of ammonia water and lithium sulfate, and the molar ratio of the reaction regulating aid to the total amount of Ni and M elements is 0.01-0.10:1.

[0067] The average particle size of the nano droplets provided by the embodiment of the present invention is controlled at 70 <D 50 <200nm.

[0068] The pyrolysis reactor provided in the embodiment of the present invention is controlled by dual temperature zones, the temperature of the front temperature zone is controlled at 150-250°C, and the temperature of the rear temperature zone is controlled at 600-1000°C;

[0069] The residence time of the nano droplets in the pyrolysis reactor is 30-120s;

[0070] The carrier gas is an oxygen-containing atmosphere, and the oxygen content is 20-100%.

[0071] A lithium-ion battery provided by an embodiment of the present invention comprises the high-nickel oxide positive electrode material described in the first and second aspects.

[0072] like Figure 5As shown, a system for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure provided by an embodiment of the present invention includes:

[0073] The preparation module is used to prepare the reaction solution: dissolve the Li source, Ni source, M source, organic complexing agent, and reaction regulating agent in deionized water to prepare the reaction solution;

[0074] The pyrolysis module is used to atomize the above reaction solution into nano droplets, which enter the pyrolysis reactor with the carrier gas. A series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally a high-nickel oxide positive electrode material with a two-phase symbiotic structure is collected at the tail end.

[0075] The method for preparing a high-nickel oxide positive electrode material with a two-phase symbiotic structure of the present invention is a process for preparing a high-nickel oxide material with a special structure through a series of steps, including preparation of a reaction solution, generation of nano droplets, and pyrolysis reaction. The specific working principle is as follows:

[0076] 1. Prepare the reaction solution

[0077] In the first step of the preparation process, the Li source, Ni source, M source, organic complexing agent (such as citric acid or urea) and reaction regulating agent (such as ammonia water or lithium sulfate) are dissolved in deionized water to prepare a uniform reaction solution. The Li, Ni and M sources provide lithium, nickel and other transition metal ions in the material, the organic complexing agent can regulate the viscosity and surface tension of the solution, and provide calorific value, and the reaction regulating agent regulates the pH value of the solution, ion transport characteristics and reaction environment. By precisely controlling the proportion of each component in the reaction solution, the elemental composition and structural characteristics of the final product are ensured.

[0078] 2. Generation and atomization control of nano droplets

[0079] The above reaction solution is atomized into nano-scale droplets with a particle size controlled between 70-200nm to ensure that the final cathode material particle size is within the range of 50-150nm. These nano droplets carry evenly distributed ions of Li, Ni, M and complexing and regulating additives and enter the pyrolysis reactor under the impetus of the carrier gas. The particle size control of the droplets is crucial to the formation of uniform and stable nanoparticles. The generation of nano-scale droplets can effectively ensure the sufficiency of the reaction in the subsequent pyrolysis process.

[0080] 3. Dual-temperature zone pyrolysis reaction and structure formation

[0081] In the pyrolysis reactor, the nano droplets undergo heating treatment in two temperature zones: the temperature in the front temperature zone is controlled at 150-250°C to complete the evaporation and drying process of the droplets and completely remove the solvent; the temperature in the rear temperature zone is controlled at 600-1000°C to complete the deposition, crystallization and phase transformation of the material. This dual-temperature zone design enables the material to obtain precise temperature control at different reaction stages. The high temperature at the rear end allows the material to simultaneously form a two-phase symbiotic structure of a layered structure and a spinel structure, in which the jagged end of the spinel structure region is wedged into the layered structure. This structure can improve the cycle stability and conductivity of the positive electrode material.

[0082] 4. Oxygen atmosphere conditions and final material formation

[0083] The carrier gas is an oxygen-containing atmosphere, and the oxygen concentration is controlled at 20-100%, providing sufficient oxidation conditions to ensure that the transition metal ions reach the ideal oxidation state during the material formation process and form a stable chemical structure. In the pyrolysis reactor, the nano droplets stay for 30-120 seconds to ensure that the reaction is fully carried out. The control of oxygen content and the setting of residence time enable the material to achieve the best state in terms of chemical structure, crystal phase, and two-phase symbiotic structure, thereby preparing a high nickel oxide positive electrode material with high electrochemical performance and structural stability.

[0084] The following are two specific application examples of the "method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure" of the present invention in the industry:

[0085] Example 1: High energy density lithium-ion battery

[0086] Application scenarios: High nickel oxide cathode materials are widely used in high energy density lithium-ion batteries, suitable for electric vehicles, power tools and large energy storage systems. The higher nickel content of high nickel materials gives the battery a higher energy density, and the two-phase symbiotic structure (coexistence of layered and spinel structures) prepared by the present invention has better stability and long life in cyclic use.

[0087] 1. Material preparation: The preparation method of the present invention is used to prepare a high nickel oxide positive electrode material with a two-phase symbiotic structure by precisely controlling the ratio of Li, Ni and M sources, the atomization particle size and the dual-temperature zone pyrolysis process, thereby ensuring its high stability and lithium ion reaction kinetics during battery formation and circulation.

[0088] 2. Battery application: The prepared cathode material is applied to the cathode of lithium-ion batteries to test its energy density, cycle life and charge and discharge performance. In electric vehicle batteries, this high nickel oxide cathode material can significantly improve the battery's range and cycle life while reducing material costs.

[0089] Compared with traditional positive electrode materials, the high nickel oxide positive electrode material of the present invention has higher energy density, better cycle stability and lower manufacturing cost, which effectively prolongs the battery life and improves the performance and user experience of electric vehicles.

[0090] Example 2: High-capacity battery pack for large energy storage power station

[0091] Application scenarios: In grid energy storage, renewable energy grid connection and microgrid systems, energy storage power stations require high-capacity, long-life batteries to regulate power supply. High nickel oxide positive electrode materials are suitable for such high-capacity battery packs because of their excellent electrochemical properties and structural stability.

[0092] 1. Large-scale production of materials: According to the needs of energy storage batteries, high nickel oxide positive electrode materials are mass-produced according to the preparation method of the present invention to ensure the uniformity and stability of the materials. By controlling the pyrolysis temperature and oxygen concentration, a two-phase symbiotic structure material with high structural stability is formed to meet the requirements of energy storage systems for material durability and high current output.

[0093] 2. Battery pack integration: Apply high nickel oxide positive electrode materials to the positive electrode of energy storage battery packs to test their performance under high rate charge and discharge and deep cycle. In energy storage power stations, battery packs with positive electrodes of this material can efficiently store and release energy, ensuring the stable operation of energy storage power stations.

[0094] The energy storage battery pack made of this high-nickel positive electrode material has high capacity, low self-discharge and long cycle life. It can meet the high stability and high efficiency requirements of energy storage power stations for batteries, reduce the overall maintenance cost of the energy storage system, and improve the grid-connected efficiency of renewable energy.

[0095] Figure 6 Comparison of the cycling performance of NCM811 materials with traditional layered structure and NCM811 materials with two-phase symbiotic structure.

[0096] The above figure is a comparison of the cycle performance of the traditional layered structure NCM811 material (NCM811-A) and the two-phase symbiotic structure NCM811 material (NCM811-B) under 3.0-4.3V, 1C conditions. It can be seen that the first cycle discharge capacity of NCM811-B is about 195.4mAh / g, which is higher than the 188.8mAh / g of NCM811-A. After 100 cycles, the capacity retention rate of NCM811-B is 98.5%, while that of NCM811-A is only 89.5%. This shows that the nano-sized two-phase symbiotic structure high nickel oxide positive electrode material has better specific capacity and cycle stability.

[0097] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure, characterized in that: The high nickel oxide positive electrode material with two-phase symbiotic structure and the preparation method thereof comprise the following steps: Step 1, preparing a reaction solution: dissolving a Li source, a Ni source, a M source, an organic complexing agent, and a reaction regulating agent in deionized water to prepare a reaction solution; Step 2, atomizing the above reaction solution into nano droplets, entering the pyrolysis reactor with the carrier gas, and a series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally a high nickel oxide positive electrode material with a two-phase symbiotic structure is collected at the tail end.

2. The method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure as claimed in claim 1, characterized in that: The high nickel oxide positive electrode material: (1) The general chemical formula of the material is LiNi x M y O2, wherein x+y=1, 0.8≤x<1, and M is one or more of Co, Mn, Al, Zr, W, Sb, Ta, and Ti; (2) The material is nanoparticles with an average particle size range of 50 <D 50 <150nm; (3) The material is a two-phase intergrowth structure of layered structure and spinel structure, in which the layered structures are wedged into each other with the jagged ends of the spinel structure region as the connection point; (4) The spinel structure belongs to the Fd-3m space group, the oxygen atoms are face-centered cubic close-packed, the transition metal ions occupy 1 / 2 of the oxygen octahedral voids, and the lithium ions occupy 1 / 8 of the oxygen tetrahedral voids.

3. The method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure as claimed in claim 1, characterized in that: The Li source is one or more of Li carboxylates, nitrates, and chlorides, and the molar ratio of Li to the total amount of Ni and M elements is 1.0-1.1:1; Wherein, the Ni source and the M source are one or more of Ni and M carboxylates, nitrates, and chlorides, respectively, and the total concentration of Ni and M ions in the reaction solution is 1-15 mol / L; The organic complexing aid is one or more of citric acid and urea, and the molar ratio of the organic complexing aid to the total amount of Ni and M elements is 0.3-0.7:1; The reaction regulating aid is one or more of ammonia water and lithium sulfate, and the molar ratio of the reaction regulating aid to the total amount of Ni and M elements is 0.01-0.10:

1.

4. The method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure as claimed in claim 1, characterized in that: The average particle size of the nano droplets is controlled at 70 <D 50 <200nm.

5. The method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure as claimed in claim 1, characterized in that: The pyrolysis reactor is controlled by two temperature zones, the temperature of the front temperature zone is controlled at 150-250°C, and the temperature of the rear temperature zone is controlled at 600-1000°C; The residence time of the nano droplets in the pyrolysis reactor is 30-120s; The carrier gas is an oxygen-containing atmosphere, and the oxygen content is 20-100%.

6. A lithium-ion battery implementing the method for preparing a high-nickel oxide positive electrode material with a two-phase symbiotic structure as described in any one of claims 1 to 5, wherein the lithium-ion battery comprises the high-nickel oxide positive electrode materials described in the first and second aspects.

7. A system for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure, which implements the method for preparing a high nickel oxide positive electrode material with a two-phase symbiotic structure as claimed in any one of claims 1 to 6, characterized in that: The high nickel oxide positive electrode material preparation system of the two-phase symbiotic structure comprises: The preparation module is used to prepare the reaction solution: dissolve the Li source, Ni source, M source, organic complexing agent, and reaction regulating agent in deionized water to prepare the reaction solution; The pyrolysis module is used to atomize the above reaction solution into nano droplets, which enter the pyrolysis reactor with the carrier gas. A series of reaction processes such as evaporation, drying, deposition, and pyrolysis occur in a very short time, and finally a high-nickel oxide positive electrode material with a two-phase symbiotic structure is collected at the tail end.

Citation Information

Cited By

  • Element and structure double-gradient high-nickel cobalt-free lithium ion battery positive electrode material as well as preparation method and application thereof

    CN120573765A